FAKTOR FAKTOR YANG MEMPENGARUHI KINE RJA PEMERINTAH KABUPATEN PIDIE - Muhammad Yusuf; Mahdani Ibrahim (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2015)
This article is an empirical research aimed to analyze the influence of discipline,compensation, and work environment on employee performance and its impact on the effectiveness of government performance Pidie. A sample of 87 employees of the government secretariat Pidie. Sampling was carried out with random sampling method in which all of the respondents in the population have an equal opportunity to be observed. Methods of data analysis using path analysis. The results showed that discipline, compensation, and work environment, partially no effect on employee performance, but simultaneously have an influence on employee performance. Furthermore, the results of the analysis also showed that either partially or simultaneously variable discipline ,compensation, and work environment are positive and significant impact on the effectiveness of government performance Pidie. In addition, the results of the analysis indicate a positive and significant effect between employee performance by enhancing the effectiveness of government performance Pidie.